Attitude of Prospective Teachers and Prospective Teacher Educators’ towards the Usage of Information and Communication Technology and its related technologies in Colleges of Teacher Education - SAIF, SHAZLI (IJRDO - Journal of Social Science and Humanities Research, 2019)
Twenty first century is the age of Information and Communication Technology (ICT). ICT has influenced all aspects of human life, teacher education cannot be exception. This fact influences the change of attitudes towards the usage of ICTs. A wide range of ICT such as laptop, Liquid Crystal Display projectors, softwares like Power Point, MS Office and several other interactive courseware are now increasingly being used by the teachers and teaching learning communities so as to support teaching and learning in the classroom. Recognizing the impact of new technologies, the teacher education institutions are trying to restr5cutre their educational programs and classroom facilities, in order to minimize the teaching and learning technology gap between the present and the future. The present study aimed at finding out the attitude of prospective teachers and prospective teacher educators towards the use of ICTs in the classrooms in relation to gender, class, habitat, discipline and medium of school. For carrying out the present study, a sample of 93 prospective teachers, which were B.Ed students and 30 prospective teacher educators, which were M.Ed students were taken. These students were from Vivekananda College of Teacher Education, Aligarh, Uttar Pradesh. Survey method was used to collect data. Data was collected with the help of self-constructed questionnaire which contained Likert type 25 items and one open ended question. The statistical techniques which used were mean, SD, t-ratio and Analysis of Variance in order to analyse the collected data. The findings of the study indicated that there was significant difference in the attitude of prospective teachers and prospective teacher educators on the basis of gender, class, medium but no significant difference was found among them, on the basis of discipline and location. The present paper also tries to find out that how ICTs would be able to transform the present teacher-centred classroom learning environment into a more innovative, rich ICT-based student-centred learning environment.